CAO CAO: A STUDY IN BEHAVIOR AND DECISION-MAKING THROUGH PERSONALITY PSYCHOLOGY THEORIES - อรสิริวรรณ บุษดี (CRMA Journal of Humanities and Social Sciences, 2021)
The objective of this article is to study the behavior and decision-making of Cao Cao in various situations and to explain them by applying the personality psychology theories of Alfred Adler, Karen Horney, and Abraham Maslow. The study found that Cao Cao’s actions arguably stemmed from basic needs, such as ambition and the desire for fame, praise, and power. In addition, Cao Cao also displays strong leadership characteristics, being cunning, perceptive, courageous, and prudent. Decisions are carefully considered, but once a decision has been made, he is completely decisive and tries to carry his action to its conclusion. These traits make him attractive to people and encourages their loyalty and contributes to his ability to overcome the odds. However, his weakness is his paranoia, which is a source of doubts and concerns that led to overly aggressive and even cruel behavior. Cao Cao’s highest desire is to reunite the kingdom under his rule. This desire was born from the 5th level of Maslow’s Hierarchy of Needs (need for self-actualization) and resulted in him having to wage war for most of his life and to be constantly alert for plots to overthrow him. Thus, Cao Cao was afflicted with severe migraines at the end of his life, as well as hallucinations. Yet, he did not give up on his desires and transmitted them to his son and heir, Cao Pi, as well as the trusted nobility.